2019
DOI: 10.1002/jcla.23048
|View full text |Cite|
|
Sign up to set email alerts
|

Association of vitamin d with glycemic control in Saudi patients with type 2 diabetes: A retrospective chart review study in an emerging university hospital

Abstract: Background Vitamin D (mainly 25‐hydroxyvitamin D, 25[OH]D) has stimulated increasing interest in Saudi Arabia over the current years due to its association with several different chronic diseases such as diabetes. This study aims to ascertain whether the vitamin D level has any influence on glycemic control in Saudi patients with type 2 diabetes (T2DM). Method This retrospective study included 200 patients with T2DM who visited Prince Sattam Bin Abdulaziz University Hospital between January 2015 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In fact, reduced 25OHVD levels were hypothesized to be involved in the pathophysiology of diabetes-related skeletal fragility [ 87 ]. Recently, low circulating VD was reported to be associated with poor glycemic control in diabetic patients [ 88 ]. Moreover, large prospective studies suggested that low VD may predispose to a higher risk of developing impaired fasting glucose and diabetes [ 89 , 90 ].…”
Section: Review Of the Evidencesmentioning
confidence: 99%
“…In fact, reduced 25OHVD levels were hypothesized to be involved in the pathophysiology of diabetes-related skeletal fragility [ 87 ]. Recently, low circulating VD was reported to be associated with poor glycemic control in diabetic patients [ 88 ]. Moreover, large prospective studies suggested that low VD may predispose to a higher risk of developing impaired fasting glucose and diabetes [ 89 , 90 ].…”
Section: Review Of the Evidencesmentioning
confidence: 99%
“…However, we demonstrated a relatively high level of poor glycemic control (48%) among patients with T1DM and T2DM. Similarly, recent studies carried out in Riyadh and Al Kharj showed that 43.13% and 44.5% of patients had uncontrolled diabetes, respectively (18,19). Other national studies have shown alarming levels in T2DM, where suboptimal HbA1c values were reported among 74.0% of patients in Jizan (20) and 73.8% in Al-Madinah(21).…”
Section: Discussionmentioning
confidence: 81%
“…Dhia J. al-Timimi et al, 2013 (23) and Khaled . Al Dossari et al, (24) study found that the diabetic patients with poor glycemic control have lower vitamin D status and higher predominance of low 25(OH) D status when compared with diabetic patients who have fair and good glycemic control. Giacomo Zoppini et al (25) found that status of vitamin D is correlated independently with Hba1c level when the adjustment for some confounding factors like diabetes period, age and glycosylated hemoglobin occur .…”
Section: Analysis Of Datamentioning
confidence: 97%